Internal and external synergetic integrated concrete protection method

Through the integrated protection method of internal and external coordinated protection, the reinforcement body is used to improve the compactness of concrete and a superhydrophobic coating with double rough structure is constructed on the surface, which solves the problem of cement concrete erosion in complex environments and significantly improves its durability and service life. .

CN119462060AActive Publication Date: 2025-02-18HARBIN INST OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411382570.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-18
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Cement concrete materials are susceptible to erosion and damage in complex environments, resulting in performance deterioration and structural failure.

Method used

The integrated internal and external protection method is adopted to enhance the compactness of the concrete through the reinforcement body, and a double rough structure of microscopic and nanoscopic rough structure is constructed on the concrete surface to form a superhydrophobic and corrosion-proof coating.

Benefits of technology

It significantly improves the durability and service life of concrete, effectively resists erosion from the external environment, and enhances its performance of resistance to seepage, chemical erosion, freeze-thaw cycle and high and low temperature cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462060A_ABST
    Figure CN119462060A_ABST
Patent Text Reader

Abstract

The invention relates to a method for protecting concrete, in particular to a method for integrally protecting concrete through internal and external cooperation. The invention aims to solve the technical problems that the performance of the conventional concrete material is gradually degraded and even the structural failure is caused because the conventional concrete material is eroded and damaged by various complex environments. The invention provides a method for integrally protecting concrete through internal and external synergism, which is realized through innovation in two aspects: firstly, the compactness and the strength of the concrete are remarkably improved through a special surface treatment process by utilizing combination of a reinforcement body and cement; and secondly, micro and nano double coarse structures are sequentially constructed on the surface of the concrete by adopting a super-hydrophobic anti-corrosion coating technology, so that an efficient super-hydrophobic layer is formed. The method provided by the invention effectively resists the erosion of the external environment, solves the problems of concrete carbonization, sulfate erosion, steel bar corrosion and the like, and provides a high-performance and long-life concrete material solution for the field of civil engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for protecting concrete. Background Art

[0002] In the field of civil engineering, cement concrete is a widely used building material, and its durability and long-term stability are directly related to the safety and life of engineering structures. However, in practical applications, cement concrete materials are often eroded and damaged by various complex environments, resulting in the gradual deterioration of their performance and even structural failure. This corrosion phenomenon is not limited to specific marine environments, but also widely exists in industrial pollution areas, around chemical plants, and areas with extreme climate changes.

[0003] The root cause of corrosion mainly comes from the interaction between external environmental factors and the physical and chemical changes inside concrete. For example, harmful gases such as carbon dioxide and sulfide in the air and dissolved salts in water can penetrate into the concrete and react with cement hydration products, leading to problems such as concrete carbonization and sulfate corrosion. In addition, climatic conditions such as extreme temperature cycles and alternating dry and wet conditions can also accelerate the expansion of microcracks in concrete, reducing its density and strength. More seriously, when the steel bars embedded in the concrete are corroded by a humid environment or harmful ions, electrochemical corrosion reactions will occur, generating rust products with expanded volume, which will further squeeze and destroy the surrounding concrete protective layer, forming a vicious cycle. This process not only weakens the bearing capacity of the structure, but may also lead to sudden destruction, posing a threat to the safety of life and property.

[0004] Therefore, the development of cement concrete materials with high anti-corrosion performance and its supporting protection technology has become an important issue that needs to be solved in the current civil engineering field. By improving the density of cement concrete itself or applying surface coating technology, the impermeability, chemical corrosion resistance and durability of concrete can be effectively improved, thereby extending the service life of the engineering structure and ensuring its safe and stable operation. Summary of the invention

[0005] The present invention aims to solve the technical problem that concrete materials are currently facing erosion and damage from various complex environments, which leads to gradual degradation of their performance and even structural failure, and to provide a method for internal and external coordinated integrated protection of concrete.

[0006] The method for the internal and external coordinated integrated protective concrete of the present invention is carried out according to the following steps:

[0007] 1. Internal protection: Provide a method for improving the density of cement concrete by using reinforcement. The specific process is as follows:

[0008] 1. Surface treatment of a reinforcement, wherein the reinforcement comprises one or a mixture of organic fibers, inorganic fibers, whiskers and carbon nanotubes;

[0009] 2. Prepare cement gel, dissolve the reinforcement treated in step 1 into a solvent, then add it into the cement gel for mixing, then pour it into a mold for forming, then solidify, demold, and cure indoors to obtain a cement concrete specimen;

[0010] 2. External protection: Using super hydrophobic anti-corrosion coating technology, a microscopic and nanoscopic double rough structure is sequentially constructed on the concrete surface to form a highly efficient anti-corrosion layer. The specific process is as follows:

[0011] 1. Microstructure construction

[0012] ①, using a solvent to dissolve the resin and curing agent, heating in a water bath and magnetic stirring to obtain a mixed solution; the mass of the resin and the curing agent is (9-12):1;

[0013] ②, then immerse the surface of the cement concrete specimen to be protected after curing in step 1 into the mixed solution for 2s to 3s, and then take it out; repeat this step twice, that is, immerse it three times in total, and obtain a bonding layer on the surface of the cement concrete specimen to be protected;

[0014] ③, the particles are evenly dispersed on the surface of the bonding layer in the cement concrete specimen through a sieve to obtain a composite material with a microscopic rough structure, and then cured;

[0015] 2. Construction of nanostructures

[0016] ① Use solvent to dissolve resin, curing agent, hydrophobic modifier and nanoparticles, heat in a water bath and stir magnetically to form a uniform super-hydrophobic suspension;

[0017] The mass ratio of the resin to the curing agent is (9-12):1; the mass ratio of the curing agent to the hydrophobic modifier is 1:1;

[0018] ②, immerse the surface of the cement concrete to be protected after being cured in step 1 into the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 1h to 1.5h;

[0019] ③. Repeat step ② once;

[0020] ④. Immerse the surface of the cement concrete to be protected after being cured in step ③ in the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 3h to 3.5h to obtain a concrete structure with coordinated integrated protection inside and outside.

[0021] The present invention provides a method for internal and external synergistic integrated protection of concrete, aiming to significantly improve the durability and service life of concrete. The invention is realized through two aspects of innovation: first, the density and strength of concrete are significantly improved by combining reinforcement with cement through special surface treatment process; second, super hydrophobic anti-corrosion coating technology is used to sequentially construct microscopic and nanoscopic double rough structures on the concrete surface to form an efficient super hydrophobic layer. The method of the present invention effectively resists the erosion of the external environment, solves the problems of concrete carbonization, sulfate corrosion and steel corrosion, and provides a high-performance, long-life concrete material solution for the field of civil engineering. The concrete structure prepared by the present invention is significantly improved in anti-corrosion performance compared to traditional cement-based materials, and at the same time shows enhanced self-cleaning, anti-icing, anti-seepage, high and low temperature cycle resistance, UV aging resistance and other properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a comparison chart of the contact angle measurement results of Experiment 5;

[0023] Figure 2 This is the data graph of the contact angle of the coating at different friction times in test six;

[0024] Figure 3 This is a photo of the coating surface of sample No. 1 in test 7 before the tape peeling test in test 3;

[0025] Figure 4 This is a photo of the coating surface of sample No. 1 in test 7 after the tape was peeled off in test 3;

[0026] Figure 5 This is a photo of the coating surface of sample No. 2 in test 7 before the tape peeling test in test 3;

[0027] Figure 6 This is a photo of the coating surface of sample No. 2 in test 7 after the tape was peeled off in comparison test 3;

[0028] Figure 7 This is a photo of the coating surface of sample No. 1 before the tape peeling test when the mass ratio of nanoparticles to anhydrous ethanol was 1:10 in Test 1 of Test 7;

[0029] Figure 8 This is a photo of the coating surface of sample No. 1 after the tape is peeled off when the mass ratio of nanoparticles to anhydrous ethanol is 1:10 in test 1 of test 7;

[0030] Fig. 9 This is a photo of the coating surface of sample No. 2 before the tape peeling test when the mass ratio of nanoparticles to anhydrous ethanol was 1:10 in Test 1 of Test 7;

[0031] Fig.10This is a photo of the coating surface of sample No. 2 after the tape is peeled off when the mass ratio of nanoparticles to anhydrous ethanol is 1:10 in test 1 of test 7;

[0032] Fig.11 The scratch images in experiment eight compared with those in experiment three;

[0033] Fig.12 This is the scratch image of the experiment 1 in experiment 8 with a mass ratio of nanoparticles to anhydrous ethanol of 1:10;

[0034] Fig.13 This is a diagram of the macroscopic morphology changes of the cement-based specimens treated differently in Experiment 9 before and after immersion. DETAILED DESCRIPTION

[0035] Specific implementation method 1: This implementation method is a method for protecting concrete by internal and external coordinated integration, which is specifically carried out in the following steps:

[0036] 1. Internal protection: Provide a method for improving the density of cement concrete by using reinforcement. The specific process is as follows:

[0037] 1. Performing surface treatment on a reinforcement, wherein the reinforcement comprises one or a mixture of organic fibers, inorganic fibers, whiskers and carbon nanotubes;

[0038] 2. Prepare cement gel, dissolve the reinforcement treated in step 1 into a solvent, then add it into the cement gel for mixing, then pour it into a mold for forming, then solidify, demold, and cure indoors to obtain a cement concrete specimen;

[0039] 2. External protection: Using super hydrophobic anti-corrosion coating technology, a microscopic and nanoscopic double rough structure is sequentially constructed on the concrete surface to form a highly efficient anti-corrosion layer. The specific process is as follows:

[0040] 1. Microstructure construction

[0041] ①, using a solvent to dissolve the resin and curing agent, heating in a water bath and magnetic stirring to obtain a mixed solution; the mass of the resin and the curing agent is (9-12):1;

[0042] ②, then immerse the surface of the cement concrete specimen to be protected after curing in step 1 into the mixed solution for 2s to 3s, and then take it out; repeat this step twice, that is, immerse it three times in total, and obtain a bonding layer on the surface of the cement concrete specimen to be protected;

[0043] ③, the particles are evenly dispersed on the surface of the bonding layer in the cement concrete specimen through a sieve to obtain a composite material with a microscopic rough structure, and then cured;

[0044] 2. Construction of nanostructures

[0045] ① Use solvent to dissolve resin, curing agent, hydrophobic modifier and nanoparticles, heat in a water bath and stir magnetically to form a uniform super-hydrophobic suspension;

[0046] The mass ratio of the resin to the curing agent is (9-12):1; the mass ratio of the curing agent to the hydrophobic modifier is 1:1;

[0047] ②, immerse the surface of the cement concrete to be protected after being cured in step 1 into the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 1h to 1.5h;

[0048] ③. Repeat step ② once;

[0049] ④. Immerse the surface of the cement concrete to be protected after being cured in step ③ in the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 3h to 3.5h to obtain a concrete structure with coordinated integrated protection inside and outside.

[0050] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the organic fiber described in step 1 includes polyester fiber, polypropylene fiber, nylon fiber and natural fiber. The rest is the same as specific implementation method 1.

[0051] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the inorganic fiber described in step 1 includes glass fiber, carbon fiber, basalt fiber and metal fiber. The rest is the same as specific implementation method 1 or 2.

[0052] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that: when the reinforcement described in step 1 is carbon fiber, the surface treatment method of the reinforcement is:

[0053] (1) Desizing of carbon fiber surface

[0054] Place the beaker containing carbon fiber and anhydrous ethanol in an ultrasonic cleaner and turn on the ultrasonic treatment mode for 60 minutes to achieve effective desizing treatment on the surface of the carbon fiber;

[0055] The carbon fiber was taken out and ultrasonically treated in deionized water for 30 min to completely remove the anhydrous ethanol remaining on the surface of the carbon fiber;

[0056] The container containing the carbon fiber is placed in an oven and the temperature is set at 60-80° C. to dry the carbon fiber until it reaches a constant weight, thereby obtaining the desizing carbon fiber.

[0057] (2) Carbon fiber heat treatment

[0058] The desizing carbon fiber is spread in a container, placed in a muffle furnace, and the temperature of the muffle furnace is set to 100° C. to 500° C. to heat treat the carbon fiber for 10 min to 30 min to complete the surface treatment of the carbon fiber. The rest is the same as the third embodiment.

[0059] Specific implementation mode 5: This implementation mode is different from specific implementation mode 1 in that the cement in the cement gel in step 1 includes silicate cement, sulphoaluminate cement, phosphate cement, high alumina cement or slag cement. The rest is the same as specific implementation mode 4.

[0060] Specific implementation method 6: This implementation method is different from specific implementation method 5 in that the indoor curing time in step 1 is 28 days and the temperature is 18° C. to 22° C. The rest is the same as specific implementation method 5.

[0061] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the curing agents used in the construction of the microstructure and nanostructure in step 2 are all amines, anhydrides, phenolic forms, isocyanates or water-based curing agents. Other aspects are the same as specific embodiment 6.

[0062] Specific embodiment eight: This embodiment differs from specific embodiment seven in that the particles in step two are quartz sand particles, silicate minerals, silicon powder or silicon dioxide microbeads; the curing in step two 1 is curing at 45° C. for 5 hours or curing at room temperature. The rest is the same as specific embodiment seven.

[0063] Specific embodiment 9: This embodiment differs from specific embodiment 8 in that the hydrophobic modifier in step 2 is polydimethylsiloxane, fluorosilane hydrophobic modifier, organosilicon hydrophobic modifier or acrylate hydrophobic modifier. Other aspects are the same as specific embodiment 8.

[0064] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that the nanoparticles described in step 2 are nano-SiO2, nano-TiO2, nano-Al2O3, carbon nanotubes, graphene nanosheets or nano-clay. Other aspects are the same as specific embodiment 9.

[0065] The present invention is verified by the following tests:

[0066] Test 1: This test is a method of internal and external coordinated integrated protection of concrete, which is carried out in the following steps:

[0067] 1. Internal protection: Provide a method for improving the density of cement concrete by using reinforcement. The specific process is as follows:

[0068] 1. Surface treatment of carbon fiber:

[0069] (1) Desizing of carbon fiber surface

[0070] A layer of carbon fiber is laid at the bottom of the dried beaker to ensure that the fibers are evenly distributed; anhydrous ethanol is added to the beaker to ensure that the liquid surface completely covers the carbon fiber; the beaker containing the carbon fiber and anhydrous ethanol is placed in an ultrasonic cleaner, and the ultrasonic treatment mode is turned on for 60 minutes to achieve effective desizing treatment on the surface of the carbon fiber; the carbon fiber is 6mm short-cut carbon fiber;

[0071] Use tweezers to remove the ultrasonically treated carbon fiber from the anhydrous ethanol and transfer it to another beaker filled with deionized water to ensure that the carbon fiber is completely immersed, and then perform ultrasonic treatment again for 30 minutes to completely remove the anhydrous ethanol remaining on the surface of the carbon fiber;

[0072] The carbon fiber that has undergone secondary ultrasonic treatment is taken out from the deionized water, and is gently spread and laid flat in a clean stainless steel container to avoid overlapping; the stainless steel container containing the carbon fiber is placed in an oven, and the temperature is set to 80°C for drying until the carbon fiber reaches a constant weight state, thereby obtaining the carbon fiber after desizing treatment;

[0073] (2) Carbon fiber heat treatment

[0074] The desizing carbon fiber is evenly and flatly spread in a stainless steel container, the stainless steel container is placed in a muffle furnace, and the temperature of the muffle furnace is set to 300° C. to heat treat the carbon fiber for 15 minutes to complete the surface treatment of the carbon fiber;

[0075] 2. Add carboxymethyl cellulose to water to completely dissolve it. The mass ratio of carboxymethyl cellulose to water is 1:400 to obtain a solvent. In this process, carboxymethyl cellulose is used as a dispersant to promote uniform dispersion of carbon fibers in the subsequent mixing step.

[0076] The carbon fiber heat-treated in step 1 is dissolved in the above-mentioned solvent, wherein the mass ratio of carbon fiber to water is 0.01:1, to obtain a carbon fiber dispersion solution. In order to ensure that the carbon fiber can be evenly dispersed in the solution, an electric stirrer is used for stirring, and the speed is set to 600 rpm;

[0077] The cementitious components of magnesium phosphate cement (cementitious components include dead-burned magnesium oxide, potassium dihydrogen phosphate and sodium borate decahydrate) are mixed, and the mass ratio of dead-burned magnesium oxide, potassium dihydrogen phosphate and borax is 4:1:0.32; the mixed cementitious components are placed in a stirring pot, and the stirring equipment is started, and mechanical dry mixing is performed at 62r / min for 5 minutes. This step is intended to pre-mix the cementitious material to a state close to being completely uniform through mechanical force; after the cementitious material is uniformly stirred, the carbon fiber dispersion solution is uniformly poured into the stirring pot, and stirring is continued for 90 seconds to form a uniform mixture, wherein the mixture is uniformly mixed with the carbon fiber dispersion solution. The mass ratio of the sum of the mass of burnt magnesium oxide, potassium dihydrogen phosphate and borax to the mass of water is 1:0.14; the mixture is quickly and evenly poured into the mold for molding (vibration). During this process, it is necessary to ensure that the material fills every corner of the mold to avoid bubbles or voids; after the molding process is completed, it is allowed to stand for 15 minutes, and the mold is removed after the material is initially solidified. The mold needs to be removed carefully to avoid damaging the specimen; after demolding, the specimen is placed indoors for natural curing for 28 days, and the curing temperature is maintained at 20°C to obtain a cement concrete specimen (size 160mm×40mm×20mm);

[0078] 2. External protection: Using super hydrophobic anti-corrosion coating technology, a microscopic and nanoscopic double rough structure is sequentially constructed on the concrete surface to form a highly efficient anti-corrosion layer. The specific process is as follows:

[0079] 1. Microstructure construction

[0080] ①, using anhydrous ethanol to dissolve epoxy resin and curing agent DETA, heating in a water bath with magnetic stirring for 5 minutes (500 rpm, 30°C) to obtain a mixed solution; the mass ratio of the epoxy resin to the curing agent is 10:1, and the mass ratio of the epoxy resin to anhydrous ethanol is 1:2;

[0081] ② Then immerse the surface to be protected (a non-exposed surface of 160 mm × 40 mm) of the cement concrete specimen cured in step 1 into the mixed solution for 2 seconds, and then take it out; repeat this step twice, that is, immerse it 3 times in total, and obtain a bonding layer on the surface to be protected of the cement concrete specimen;

[0082] ③, quartz sand particles of 40-60 mesh were evenly dispersed on the surface of the bonding layer in the cement concrete specimen through a 60-mesh sieve to obtain a composite material with a microscopic rough structure, and cured at 45°C for 5h;

[0083] 2. Construction of nanostructures

[0084] ①, using anhydrous ethanol to dissolve epoxy resin, curing agent DETA, polydimethylsiloxane (Part A mass: Part B mass = 10:1) and nanoparticles, heating in a water bath with magnetic stirring for 30 minutes (300 rpm, 30° C.), to form a uniform super-hydrophobic suspension; the nanoparticles are nano-SiO2;

[0085] The mass ratio of the epoxy resin to the curing agent DETA is 10:1; the mass ratio of the epoxy resin to anhydrous ethanol is 1:10; the mass ratio of the curing agent DETA to polydimethylsiloxane is 1:1; the mass ratio of the nanoparticles to anhydrous ethanol is (3, 5, 8, 10 and 12):100 respectively, and the 5 ratios are for comparison;

[0086] ②, immerse the surface of the cement concrete to be protected after being cured in step 1 into the super-hydrophobic suspension for 2 seconds, take it out and cure it for 1 hour, and the curing temperature is 45°C;

[0087] ③. Repeat step ② once;

[0088] ④. Immerse the surface of the cement concrete to be protected after being cured in step ③ in the super-hydrophobic suspension for 2 seconds, take it out and cure it for 3 hours at a curing temperature of 45°C to obtain a concrete structure with coordinated integrated protection inside and outside.

[0089] Comparative test 1: The difference from test 1 is that in step ③ of nanostructure construction, the process of step ② is repeated 0 times, and then cured for 4 hours in step ④. The rest is the same as test 1, that is, two cycles.

[0090] Comparative experiment 2: The difference from experiment 1 is that in step ② of nanostructure construction, curing is performed for 5 hours, and steps ③ and ④ are omitted, which is one cycle. The rest is the same as experiment 1.

[0091] Experiment 2: This experiment is different from Experiment 1 in that the nanoparticles described in step 2 are nano-TiO2. The rest is the same as Experiment 1.

[0092] Experiment 3: This experiment is different from Experiment 1 in that the nanoparticles are nano-Al2O3. The rest is the same as Experiment 1.

[0093] Comparative experiment three: The difference from experiment three is that in step ③ of nanostructure construction, the process of step ② is repeated 0 times, and then cured for 4 hours in step ④. The rest is the same as experiment three, that is, two cycles.

[0094] Experiment 4: This experiment is different from Experiment 1 in that the nanoparticles are carbon nanotubes. The rest is the same as Experiment 1.

[0095] Experiment 5: The contact angle of the super-hydrophobic coating prepared in Experiment 1, Experiment 2, Experiment 3, Experiment 4, Comparative Experiment 1 and Comparative Experiment 2 was measured using a wetting angle meter. The volume of the water droplet used in the test was controlled to be 0.8μL~1μL, and the contact angle measurement value was the average of the data measured at two different positions on the super-hydrophobic surface. The contact angle was calculated and tested and analyzed by the software provided by the contact angle meter. The results are shown in the figure. Figure 1 , the concentration of nanomaterials indicates the mass fraction of nanoparticles in anhydrous ethanol. By comparing the contact angle data of super-hydrophobic coating materials prepared by the same type of nanomaterials and the same number of treatments, it is found that for nano-SiO2, the contact angle shows an upward trend as the concentration increases, and the contact angle decreases when the concentration is greater than 10%, that is, 10% is the optimal concentration of nano-SiO2. Among them, there are three groups of parameters that meet the super-hydrophobic condition (contact angle greater than 150 °): SiO2-8%-cycle three times, SiO2-10%-cycle once, and SiO2-10% cycle three times. Similarly, the optimal concentration of nano-TiO2 is also 10%. However, under the premise of keeping the experimental conditions consistent, it is observed that the contact angle data of TiO2 is always lower than the corresponding values ​​of SiO2 and Al2O3 nanomaterials. For nano-Al2O3, its contact angle data is always on the rise.

[0096] Test 6: Prepare 800# sandpaper and place it with the rough surface facing down on the coating surface of the specimen. Place a 200g standard weight on the sandpaper and use your hand to pull the sandpaper horizontally on the specimen at a constant speed. The position of the sandpaper where the weight is located completely rubs the coating surface as one friction cycle. Measure the change in contact angle of the super-hydrophobic coating after different friction cycles, and use the contact angle as an evaluation index to evaluate the friction and wear resistance of the super-hydrophobic coating. The change in the contact angle of the coating under different friction times is shown in Figure 2 ,▲ represents the mass ratio of nanoparticles to anhydrous ethanol in experiment 1, which is 1:10;◆ represents comparative experiment 3. It can be seen from the figure that under the same test conditions, the contact angle of the coating with parameters of 12%-Al2O3-cycled twice is always maintained at a higher level than that of the coating with parameters of 10%-SiO2-cycled three times, which indicates that the coating with 12%-Al2O3-cycled twice has better hydrophobic properties. In addition, the contact angle fluctuation range of the coating with 12%-Al2O3-cycled twice is smaller, reaching a maximum of 153.5° and a minimum of 146.5°, with a difference of only 7°, while the contact angle of the coating with 10%-SiO2-cycled three times has a larger range of variation, from the highest 151.5° to the lowest 140.5°, with a difference of 11°. This comparison shows that the coating with 12%-Al2O3-cycled twice exhibits better stability during friction and wear.

[0097] Test 7: To enhance the reliability of data and reduce test errors, two specimens were selected as parallel samples for each coating ratio for testing. After the coating was completely cured, 64 square grids of 2mm×2mm were evenly scratched on the surface of the sample using a grid knife device, and then the debris from the scratches was removed with a brush. Finally, 3M tape was evenly adhered to the small squares, and the tape was quickly removed from the coating surface after waiting for 2 minutes. The adhesion of the super-hydrophobic coating was evaluated by the integrity of the paint film in the grid. The test results are shown in Tables 1 and Figure 3-Figure 10 As shown, Figure 3 For comparison, the coating surface photo of sample No. 1 in test 3 before the tape peeling test is shown below. Figure 4 For comparison, the coating surface photo of sample No. 1 in test 3 after the tape was peeled off. Figure 5 For comparison, the coating surface photo of sample No. 2 in test 3 before the tape peeling test is shown below. Figure 6 For comparison, the coating surface photo of sample No. 2 in test 3 after the tape was peeled off. Figure 7 This is a photo of the coating surface of sample No. 1 before the tape peeling test when the mass ratio of nanoparticles to anhydrous ethanol is 1:10 in test 1. Figure 8 This is a photo of the coating surface of sample No. 1 after the tape is peeled off when the mass ratio of nanoparticles to anhydrous ethanol is 1:10 in test 1. Fig. 9 This is a photo of the coating surface of sample No. 2 before the tape peeling test when the mass ratio of nanoparticles to anhydrous ethanol was 1:10 in test 1. Fig.10 This is a photo of the coating surface of sample No. 2 after tape stripping when the mass ratio of nanoparticles to anhydrous ethanol was 1:10 in test 1. It can be seen that both coatings have strong substrate adhesion. The reason is that the adhesive layer epoxy resin at the bottom of the coating is a thermosetting resin, and its highly cross-linked three-dimensional network structure gives the epoxy resin excellent bonding properties and presents good mechanical robustness against tape stripping.

[0098] Table 1 Tape peeling test results

[0099]

[0100] Test 8: Starting from the hardest pencil, scratch the coatings of Test 1 and Comparative Test 3 in turn until the selected pencil does not scratch the coating, which is recorded as the hardness of the coating, see Table 2, Fig.11 and Fig.12 , Fig.11 To compare the scratch image of experiment 3, Fig.12This is the scratch image of the mass ratio of nanoparticles to anhydrous ethanol of 1:10 in experiment 1. As can be seen from the figure, the coating with parameters of 10%-SiO2-cycled three times has better hardness than the coating with parameters of 12%-Al2O3-cycled twice, and the hardness grade is increased to 6H. This may be due to the high hardness characteristics of SiO2 and its uniform distribution and good bonding in the coating, combined with the three-cycle preparation process, which together contributed to the significant improvement of the coating hardness.

[0101] Table 2 Comparison of hardness of coating samples with different parameters

[0102]

[0103] Test 9: The cement test block of the comparative test 3 and the cement test block not coated with the super-hydrophobic coating (the product after internal protection in step 1 of test 1) was placed in a NaCl solution with a mass concentration of 3.5%. Table 3 below shows the change in contact angle of the coating after immersion for 30 days. Fig.13 This is a diagram of the macroscopic morphology changes of cement-based test blocks that have been treated differently before and after immersion. Observation found that there was no obvious change in the surface morphology.

[0104] Table 3 Variation of coating contact angle with immersion time (unit: °)

[0105]

[0106] Test 10: Freeze-thaw cycle test: The samples were placed in a freeze-thaw cycle test chamber to test the change in contact angle of the coating and the change in the bonding force between the coating and the substrate to evaluate the coating's ability to resist freeze-thaw, see Tables 4 and 5 below.

[0107] Table 4 Variation of coating contact angle with freeze-thaw cycle number (unit: °)

[0108]

[0109] Table 5 Changes in the bonding strength between the coating and the substrate with the number of freeze-thaw cycles

[0110]

[0111] According to the comparative analysis of the data in the table, the change in the surface contact angle of the coating treated with 12%-Al2O3-cycles twice in the comparative test 3 after 50 freeze-thaw cycle tests is not as significant as that of the coating treated with 10%-SiO2-cycles three times in the test 1. However, it is worth noting that the former has a more significant attenuation in terms of bonding strength, indicating that although it has a certain advantage in terms of freeze-thaw cycle resistance over contact angle stability, it suffers a greater impact on the bonding strength between the coating and the substrate.

Claims

1. A method for protecting concrete by coordinated integration of inside and outside, characterized in that The method of internal and external synergistic integrated protective concrete is carried out in the following steps:

1. Internal protection: Provide a method for improving the density of cement concrete by using reinforcement. The specific process is as follows: (1) performing surface treatment on a reinforcement, wherein the reinforcement comprises one or a mixture of organic fibers, inorganic fibers, whiskers and carbon nanotubes; (2) preparing cement gel, dissolving the reinforcement treated in step 1 into a solvent, then adding it into the cement gel for mixing, then pouring it into a mold for forming, then curing, demolding, and curing indoors to obtain a cement concrete specimen; 2. External protection: Using super hydrophobic anti-corrosion coating technology, a microscopic and nanoscopic double rough structure is sequentially constructed on the concrete surface to form a highly efficient anti-corrosion layer. The specific process is as follows: (1) Microstructure ①, using a solvent to dissolve the resin and curing agent, heating in a water bath and magnetic stirring to obtain a mixed solution; the mass of the resin and the curing agent is (9-12):1; ②, then immerse the surface of the cement concrete specimen to be protected after curing in step 1 into the mixed solution for 2s to 3s, and then take it out; repeat this step twice, that is, immerse it three times in total, and obtain a bonding layer on the surface of the cement concrete specimen to be protected; ③, the particles are evenly dispersed on the surface of the bonding layer in the cement concrete specimen through a sieve to obtain a composite material with a microscopic rough structure, and then cured; (2) Construction of nanostructures ① Use solvent to dissolve resin, curing agent, hydrophobic modifier and nanoparticles, heat in a water bath and stir magnetically to form a uniform super-hydrophobic suspension; The mass ratio of the resin to the curing agent is (9-12):1; the mass ratio of the curing agent to the hydrophobic modifier is 1:1; ②, immerse the surface of the cement concrete to be protected after being cured in step 1 into the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 1h to 1.5h; ③. Repeat step ② once; ④. Immerse the surface of the cement concrete to be protected after being cured in step ③ in the super-hydrophobic suspension for 2s to 3s, take it out and cure it for 3h to 3.5h to obtain a concrete structure with coordinated integrated protection inside and outside.

2. The method for protecting concrete by internal and external coordinated integration according to claim 1 is characterized in that The organic fibers described in step 1 include polyester fibers, polypropylene fibers, nylon fibers and natural fibers.

3. The method for protecting concrete by internal and external coordinated integration according to claim 1 is characterized in that The inorganic fibers described in step 1 include glass fibers, carbon fibers, basalt fibers and metal fibers.

4. The method for protecting concrete by coordinated integration of inside and outside according to claim 3 is characterized in that When the reinforcement described in step 1 is carbon fiber, the surface treatment method of the reinforcement is: (1) Desizing of carbon fiber surface Place the beaker containing carbon fiber and anhydrous ethanol in an ultrasonic cleaner and turn on the ultrasonic treatment mode for 60 minutes to achieve effective desizing treatment on the surface of the carbon fiber; The carbon fiber was taken out and ultrasonically treated in deionized water for 30 min to completely remove the anhydrous ethanol remaining on the surface of the carbon fiber; The container containing the carbon fiber is placed in an oven and the temperature is set at 60-80° C. to dry the carbon fiber until it reaches a constant weight, thereby obtaining the desizing carbon fiber. (2) Carbon fiber heat treatment The desizing carbon fiber is spread in a container, placed in a muffle furnace, and the temperature of the muffle furnace is set to 100° C. to 500° C. to perform heat treatment on the carbon fiber for 10 to 30 minutes to complete the surface treatment of the carbon fiber.

5. The method for protecting concrete by coordinated integration of inside and outside according to claim 1 is characterized in that The cement in the cement gel described in step 1 includes silicate cement, sulphoaluminate cement, phosphate cement, high alumina cement or slag cement.

6. The method for protecting concrete by coordinated integration of inside and outside according to claim 1 is characterized in that The indoor curing time in step 1 described in step 1 is 28 days, and the temperature is 18°C ​​to 22°C.

7. The method for protecting concrete by coordinated integration of inside and outside according to claim 1 is characterized in that The curing agent in the construction of the microstructure and nanostructure described in step 2 is an amine, anhydride, phenolic, isocyanate or water-based curing agent.

8. The method for protecting concrete by coordinated integration of inside and outside according to claim 1 is characterized in that The particles described in step 2 are quartz sand particles, silicate minerals, silicon powder or silicon dioxide microbeads; the curing in step 2 1 is curing at 45° C. for 5 hours or curing at room temperature.

9. The method for protecting concrete by coordinated integration of inside and outside according to claim 1, characterized in that The hydrophobic modifier described in step 2 described in step 1 is polydimethylsiloxane, a fluorosilane hydrophobic modifier, an organosilicon hydrophobic modifier or an acrylate hydrophobic modifier.

10. The method for protecting concrete by coordinated integration of inside and outside according to claim 1, characterized in that The nanoparticles described in step 2 described in step 1 are nano-SiO2, nano-TiO2, nano-Al2O3, carbon nanotubes, graphene nanosheets or nano-clay.

Citation Information

Patent Citations

  • Hydrophobic stain-resistant coating for hydraulic concrete surfaces and method for constructing hydrophobic stain-resistant coating

    CN106318053A

  • Salt corrosion resistant concrete and preparation method thereof

    CN114014613A

  • Salt-resistant pavement cement concrete based on ion blocking effect and preparation method thereof

    CN117361962A

  • Coated fibers for enhanced concrete structural reinforcement

    US20190256418A1